Electrokinetics of suspended charged particles taking into account the excluded volume effect - Aranda Rascon, Miguel Jesus (2009)
In two recent works [López-García et al., J. Colloid Interface Sci. 316 (2007) 196; López-García et al., J. Colloid Interface Sci. 323 (2008) 146] we presented a simple modification of the standard electrokinetic model that takes into account the finite size of ions in the electrolyte solution. In the first we presented numerical results for the equilibrium properties while, in the second, we calculated the effect of the excluded ion volume on the electrophoretic mobility. In the present work we first extend our previous results incorporating a distance of closest approach of the ions to the particle surface. We then calculate the conductivity increment and present a detailed interpretation of the mobility and conductivity increment results, based on the analysis of the equilibrium and field-induced ion concentrations and of the convective fluid flow in the neighborhood of the particle surface. We show that the inclusion of the ion size effect generally improves the predictions of the standard electrokinetic model: both the electrophoretic mobility and the conductivity increment increase. We also show that, largely due to the above-noted extension of considering a minimum approach distance between the ions and the particle surface, the excluded volume effect is not negligible even for weakly charged particles.